Etnografi Lembaga Pemasyarakatan: Adaptasi, Resistensi & Penghukuman - A. Josias Simon (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2018)
This paper is the result of the author's research on Ethnography Penal Institution as a place of imprisonment execution. Adaptation and Resistance in prison life reflect the existence of the social structure and social status of prisoners. The semi-autonomous policy integrates the standard of fixed procedures and the use of adaptation networks to overcome the limitations faced by prisoners.